The Permethrin Use and Personal Hygiene Practices on the Incidence of Recurrent Scabies in the Regional Technical Implementation Unit (UPTD) X Trenggalek, Indonesia - Ayuningtyas, Aulia Putri; Tunjungsari, Feny; Handaja, Djaka (Universitas Airlangga, 2025)
Highlights: Scabies is ranked third out of the 12 most common skin diseases in Indonesia. The main assessments for scabies, based on the World Health Organization (WHO), include the use of 5% permethrin cream. Abstract Introduction: Scabies is an infectious skin disease caused by infection with the parasite Sarcoptes scabiei var. hominis. This study examined the relationship between permethrin use and personal hygiene practices on the incidence of scabies in the Regional Technical Implementation Unit (UPTD) X Trenggalek, Indonesia. Methods: This was an observational analytic study with a cross-sectional design, utilizing medical records and questionnaires collected from July to August 2023 in Trenggalek, Indonesia. The samples were the medical records of UPTD X Trenggalek, Indonesia. Results: Twenty-seven respondents were employed in this study. The highest number of respondents was males, totaling 63% of all respondents. The age of the majority of respondents ranged from 2 to 11 years old, with 48.1% of all respondents. The majority of respondents (74.1%) use permethrin as recommended. There was a significant relationship (p=0.000) between the personal hygiene variable and the incidence of scabies, with a correlation coefficient between the two variables (r=0.581). There was a significant relationship (p=0.001) between the personal hygiene variable and the incidence of scabies, with a correlation coefficient between the two variables (r=0.537). Conclusion: A significant relationship was found between permethrin use and personal hygiene on the incidence of scabies, which was observed simultaneously with a strong correlation.